1999
DOI: 10.1002/(sici)1096-9063(199905)55:5<524::aid-ps937>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between physical and chemical constraints on pesticide and water movement into and out of soil aggregates

Abstract: A laboratory experiment comparing the movement of 3 H 2 O and [14 C]isoproturon into and release from soil aggregates is described. Small aggregates (2.0±2.4 mm) were prepared from a clay topsoil and maintained at three different initial moisture conditions. A small volume of the radioisotope solution was introduced prior to bathing the aggregates in a 2 mM CaCl 2 solution to represent new rainwater. Whilst the 3 H 2 O was imbibed by the air-dry aggregates, the pesticide did not follow the water but remained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Natural soils are exposed to dynamic variations in temperature and moisture. Changes in moisture status may affect soil properties like water content or volumetric swelling of soil organic matter (SOM) [1,2] or sorbent properties [2][3][4][5]. Furthermore, the extractability of organic pollutants was found to be affected by the hydration time of soils indicating physical and physicochemical changes of SOM upon swelling [2].…”
Section: Introductionmentioning
confidence: 99%
“…Natural soils are exposed to dynamic variations in temperature and moisture. Changes in moisture status may affect soil properties like water content or volumetric swelling of soil organic matter (SOM) [1,2] or sorbent properties [2][3][4][5]. Furthermore, the extractability of organic pollutants was found to be affected by the hydration time of soils indicating physical and physicochemical changes of SOM upon swelling [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, an increasing number of studies have shown that the water content, the hydration time and drying-remoistening cycles affect sorption parameters of organic pollutants: High soil moisture enhanced sorption velocity for diuron and isoproturon and increased the final sorption for diuron (Gaillardon 1996). The release of isoproturon from soil samples was probably controlled by non-equilibrium sorption/desorption from air-dry aggregates, while a combination of nonequilibrium sorption/desorption and diffusion was needed to describe the release from wet aggregates (Johnson et al, 1999). Effects of the water status on the sorption mechanism of chlortoluron were found within up to three weeks of hydration (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hydration-induced changes in the macromolecules' mobility (Schaumann and LeBoeuf, 2005) may affect the retention of nutrients and pollutants by minerals coated with organic matter. The ability of soils and soil organic matter to sorb or release organic pollutants has been shown to depend on the state of hydration, hydration time, wetting and drying cycles, and the water content of the samples (Gaillardon, 1996;Altfelder et al, 1999;Johnson et al, 1999;Schaumann et al, 2004). In addition, the structure of organic matter can be affected by the dehydration technique applied in the laboratory, e.g., prior to sorption experiments (Altfelder et al, 1999).…”
Section: Introductionmentioning
confidence: 99%